Astronomical spectroscopy : an introduction to the atomic and molecular physics of astronomical spectra - Tennyson, Jonathan (Cambridge, Cambridge University Press, 2011)
(3z(BThe pace is suitable for a novice, the explanations are clear and the rich level of black and white diagrams are used very well to augment and illustrate the text $1! = (BFor undergraduates in astrophysics, physics in general, and even chemistry, Tennyson's book is to be recommended. Even if not used as a primary text it would be useful to augment atomic (and even molecular) spectroscopy courses with applications and examples.(3y (BContemporary Physics Review of the First Edition (3z(BWithout a doubt Astronomical Spectroscopy is the best book to read for anyone who is embarking on research in astronomical spectroscopy, as well as being the obvious text for an introductory course. It should certainly be on the shelves of every university and observatory library.(3y (BContemporary Physics Nearly all information about the Universe comes from the study of light as it reaches us. However, understanding the information contained in this light requires both telescopes capable of resolving it into its component colours and a detailed knowledge of the quantum mechanical behaviour of atoms and molecules. This book, which is based on a third-year undergraduate course taught by the author at University College London, presents the basic atomic and molecular physics necessary to understand and interpret astronomical spectra. It explains how and what kind of information can be extracted from these spectra. Contemporary astronomical spectra are used extensively to study the underlying atomic physics and illustrate the results.s
Bibliography 215-216p.; Index 217-223p.
Keywords: Astronomy; Atomic physics; Atomic spectra; Spectroscopy; Physics